Contract farming towards social business: A new paradigm - Abbasi, I.A. (MDPI, 2021)
The current paper conceptualises an innovative, sustainable social business contract farming model by blending three essential business aspects, namely, relational norms, social capital, and social business dimensions. In the case of contract farming, evidence shows that the social aspect and social businessâbased contract farming model are overâsighted. This study offers an efficient social business contract farming model by, first, reviewing the conventional contract farming model and, secondly, by developing and proposing a robust, multidimensional model for contract farming. This proposed framework may have profound implications for the agriculture sector and may pro-vide a strong sustainable contract farming management guideline for the global agriculture indus-try. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.